Elevating Arabic Speaking Skills: Plotagon and Digital Comics as Catalysts for Enhanced Learning Engagement and Proficiency - M. Kholis Amrullah; Agus Riwanda; Marsiah Marsiah; Wisetrat Wilailak (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2024)
Active student participation and engagement in diverse practice exercises are essential for mastering all four language skills. Due to the lack of active participation, students' proficiency in Arabic language learning, particularly in speaking skills (maharah kalam), falls below the required educational benchmarks. This research uses a quasi-experimental approach to assess the effectiveness of two different learning media: Plotagon for Tenth-grade students of IPS 1 and digital comics for Tenth-grade students of IPS 2 in improving Arabic speaking skills. The research findings indicate that students who used Plotagon as a learning tool to enhance their speaking skills achieved significantly better learning outcomes on average compared to students who used digital comics for the same purpose. Additionally, this study found that students who utilized Plotagon for learning exhibited higher engagement levels than those who used digital comics. These findings highlight the significance of active engagement in learning Arabic and indicate that Plotagon animation can be a valuable tool for enhancing learning outcomes and student engagement.